Continuum Model Analysis of QCM Nanotribological Data to Obtain Friction Coefficients for 304SS Contacts Lubricated by Water and TiO2 Nanoparticle Suspensions - Seed, Caitlin M.; Acharya, Biplav; Krim, Jacqueline (Frontiers in Mechanical Engineering, 2020)
We report a study of the response of a Quartz Crystal Microbalance (QCM) to rubbing contacts in air, water and aqueous suspensions of 40nm TiO2 nanoparticles. Measurements were performed with a contact comprised of 3 close-packed 304SS ball bearings situated symmetrically about the center of a 304SS QCM electrode with 2nm rms roughness. Two continuum methods were employed to infer macroscale friction coefficients μ employing QCM nanotribological data recorded in the Cattaneo-Mindlin (CM) slip regime at vibrational amplitudes that varied between 1nm and 17nm. The “slope” Method 1 involved sweeps of the QCM amplitude of vibration as ball bearings were held in continuous contact with the oscillating electrode. The “contact” Method 2 obtained μ by analyzing the shifts in frequency and bandwidth that occur at a fixed uo to solve for μ. when ball bearings were brought in and out of contact with the QCM’s electrode. The results for dry and water lubricated contacts compared favorably with macroscale friction coefficients reported in the literature. The model failed to adequately describe contacts lubricated with the NP suspension, but its continuum nature did not appear to be the dominant factor underlying failure. The failure was more likely attributable to either a lack of a CM slip regime when NP were present at the interface and/or the fact that the amplitude of vibration was close in size to the individual NP contacting regions, in violation of a key underlying assumption of the model.